2021
DOI: 10.3390/antiox10010107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TGF-β by Induced Oxidative Stress in Human Trabecular Meshwork Cells

Abstract: Oxidative stress generated by reactive oxygen species (ROS) plays a critical role in the pathomechanism of glaucoma, which is a multifactorial blinding disease that may cause irreversible damage within human trabecular meshwork cells (HTMCs). It is known that the transforming growth factor-β (TGF-β) signaling pathway is an important component of oxidative stress-induced damage related to extracellular matrix (ECM) fibrosis and activates cell antioxidative mechanisms. To elucidate the dual potential roles and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…For the evaluation of the drug efficacy of brimonidine (BRI), an α2-adrenergic agonist on TGF-β2 (5 ng/mL)-treated HTM cells (2D and 3D) 10 μM BRI were supplemented on cell culture day 1. The drug concentrations were confirmed as the optimal concentrations based on previous studies [ 11 , 13 , 14 ], and a cell viability analysis of BRI using retinal pigment epithelium cells [ 15 ].…”
Section: Methodssupporting
confidence: 64%
“…For the evaluation of the drug efficacy of brimonidine (BRI), an α2-adrenergic agonist on TGF-β2 (5 ng/mL)-treated HTM cells (2D and 3D) 10 μM BRI were supplemented on cell culture day 1. The drug concentrations were confirmed as the optimal concentrations based on previous studies [ 11 , 13 , 14 ], and a cell viability analysis of BRI using retinal pigment epithelium cells [ 15 ].…”
Section: Methodssupporting
confidence: 64%
“…Especially in the CCl 4 -induced liver injury model, several studies indicate that natural products can alleviate tissue injury by modulating immune responses and oxidative stress [43][44][45][46]. TGF-β1 is well known for regulating inflammation and oxidative stress [47,48]. In other words, TGF-β1 can be associated with the process of liver injury by mediating inflammation and oxidative stress, for example, downregulation of miR-10a can suppress sepsis-induced liver injury by downregulating the TGF-β1 pathway, as well as inflammation and oxidative stress [49].…”
Section: Discussionmentioning
confidence: 99%
“…In podocytes TGF-β induces the synthesis and release of EDN1 which initiates mitochondrial ROS, mitochondrial DNA damage and mitochondrial dysfunction 68 . Similarly, there is an interplay between ROS and TGF-β in glaucoma 69 , and NOX4 is one of the major sources of cellular oxidative stress and is an important downstream effector in mediating TGF-β-induced fibrosis in the heart, lungs and kidneys via the production of ROS 70 . NOX4 was significantly upregulated by TGF-β2 in our study and has been demonstrated to drive ECM production, actin stress fibre formation and αSMA expression in the TM 71 .…”
Section: Discussionmentioning
confidence: 99%